Diferensiasi Gelatin Sapi dan Gelatin Babi pada Gummy Vitamin C Menggunakan Metode Kombinasi Spektroskopi Fourier Transform Infrared (FTIR) dan Principal Component Analysis (PCA) - Zilhadia, Zilhadia; Kusumaningrum, Farida; Betha, Ofa Suzanti; Supandi, Supandi (UI Scholars Hub, 2018)
Gelatin is a polypeptide obtained by partial hydrolysis of collagen derived from skin and bones of bovine and porcine. It has an essential component for the manufacture of gummy vitamin C as a gel-forming agent. The porcine gelatin is haram for moslems. This study was conducted to differentiate bovine gelatin and porcine gelatin in vitamin C gummy by using Fourier Transform Infrared (FTIR) combined with PCA. Gelatin was extracted from vitamin C gummy by using acetone at -20ºC and analyzed at wave number 4000-750 cm-1. The spectrum of both bovine and porcine gelatin extract from vitamin C gummy have almost the same number absorption that can not be distinguished. Therefore, the spectrum was analyzed by PCA. PCA result, represented with the plot score, showed that both bovine and porcine gelatin extracted has a clear dictinction. PCAcombined FTIR could differentiate of them. This study obtained that the commercial vitamin C gummy contained bovine gelatin.